News of Organizations and Institutions (Academy of Management Journal, 1961)
Presents news briefs on organizations and institutions devoted to management as of August 1961. Development of a new core curricula by the College of Business Administration and the Department of Management at the University of Florida; Publication of academic journal by the Institute of Industrial Relations at the University of California; Sponsorship of a national placement service for college and university administrative officials by the College and University Personnel Association.